2017
DOI: 10.1063/1.5006029
|View full text |Cite
|
Sign up to set email alerts
|

Work function and surface stability of tungsten-based thermionic electron emission cathodes

Abstract: Materials that exhibit a low work function and therefore easily emit electrons into vacuum form the basis of electronic devices used in applications ranging from satellite communications to thermionic energy conversion. W-Ba-O is the canonical materials system that functions as the thermionic electron emitter used commercially in a range of high power electron devices. However, the work functions, surface stability, and kinetic characteristics of a polycrystalline W emitter surface are still not well understoo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…Dewetting is a self-regulating phenomenon that ensures a thin layer of barium on the surface. Recent theoretical studies [5] find that Ba is unstable on the clean tungsten low index surfaces, consistent with dewetting. In the work shown by Zhou et al [20], similar calculations show that barium adsorption on clean tungsten is unstable relative to the Ba-oxides on W (100), W (111) and W (112).…”
Section: Introductionmentioning
confidence: 70%
“…Dewetting is a self-regulating phenomenon that ensures a thin layer of barium on the surface. Recent theoretical studies [5] find that Ba is unstable on the clean tungsten low index surfaces, consistent with dewetting. In the work shown by Zhou et al [20], similar calculations show that barium adsorption on clean tungsten is unstable relative to the Ba-oxides on W (100), W (111) and W (112).…”
Section: Introductionmentioning
confidence: 70%
“…The generally accepted mechanisms for the improved performance are "dipole model" [40] and "excess barium adsorption model" [41] with the emphasized function of active Ba. According to these works, Ba first diffuses from the inside of the matrix to W surface through the pores to form the Ba-O dipole layer at high temperatures, which leads to a sharp decrease of the work function and promotes the electron emission.…”
Section: B-type Cathodementioning
confidence: 99%
“…In recent years, DFT methods were applied to investigate the work function and surface stability of cathodes [40]. The model that combined the work function of different surface grain orientations was further developed, which is calculated according to the area fractions of different surface grain orientations in real polycrystalline W specimens provided via electron backscatter diffraction (EBSD) microscopy [44].…”
Section: B-type Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that the Ba 0.25 Sc 0.25 O structure is the most stable structure and holds the lowest work function compared to other Ba x Sc y O z monolayers. They found that in the W-Ba-W system the most stable surface adsorbates were Ba-O species with compositions in the range of Ba 0.125 O-Ba 0.25 O per surface of a W atom, and Ba could form work function-lowering surface dipoles [53].…”
Section: Mechanism Study Of the Sdi Cathodementioning
confidence: 99%